2014
DOI: 10.1371/journal.pone.0087629
|View full text |Cite
|
Sign up to set email alerts
|

[18F]FDG Positron Emission Tomography within Two Weeks of Starting Erlotinib Therapy Can Predict Response in Non-Small Cell Lung Cancer Patients

Abstract: PurposeThe aim of this prospective study was to evaluate whether [18F]FDG-PET/CT, performed within two weeks of starting erlotinib therapy can predict tumor response defined by RECIST 1.1 criteria after 8 weeks of treatment in patients with inoperable (stage IIIA to IV) non-small cell lung cancer patients.Patients and MethodsThree [18F]FDG-PET/CT scans were acquired in 12 patients before (5±4 days) and after 9±3 days (early PET) and 60±6 days (late PET) of erlotinib therapy. Conventional evaluation, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 37 publications
(43 reference statements)
2
22
0
2
Order By: Relevance
“…PET detection of new lesions early in the course of therapy has been reported to be a strong, independent predictive factor for overall survival in NSCLC patients treated with EGFR inhibitor (Aukema et al, 2010). In our study, small-animal PET/CT also confirmed that GEF-NPs has superior antitumor effect, as compared with free GEF or control group, GEF-NPs group had the lowest tumor uptake, which has a prognostic value in NSCLC (Hachemi et al, 2013). Furthermore, no new lesions detected by micro-PET early in the course of therapy were observed, in accordance with the result of survival analysis.…”
Section: Discussionsupporting
confidence: 78%
“…PET detection of new lesions early in the course of therapy has been reported to be a strong, independent predictive factor for overall survival in NSCLC patients treated with EGFR inhibitor (Aukema et al, 2010). In our study, small-animal PET/CT also confirmed that GEF-NPs has superior antitumor effect, as compared with free GEF or control group, GEF-NPs group had the lowest tumor uptake, which has a prognostic value in NSCLC (Hachemi et al, 2013). Furthermore, no new lesions detected by micro-PET early in the course of therapy were observed, in accordance with the result of survival analysis.…”
Section: Discussionsupporting
confidence: 78%
“…There was also a report that in iodine-refractory differentiated thyroid cancer, an early 18 F-FDG PET response was useful for identifying sorafenib non-responders, although no BRAF mutation analysis was performed in those patients [29]. As for other targeted agents, such as gefitinib and erlotinib for lung cancer [30][31][32][33], 18 F-FDG PET/CT may have a role in BRAF mutant PTC treated with sorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients carrying mutations of the EGFR gene generally respond better to tyrosine kinase inhibitors (TKIs) [1], erlotinib may improve survival even in subjects with EGFR wild-type tumors [2]. Several studies have shown that FDG-PET is a useful imaging modality for predicting response to erlotinib in patients with non-small cell lung cancer (NSCLC) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. However, most of these studies used only the primary tumor as the target lesion for sequential imaging [3][4][5][6][7][8][9][10][11][12], and treatment response was largely assessed using the European Organization for Research and Treatment of Cancer (EORTC) criteria [3][4][5][6][7][8][9]20].…”
Section: Introductionmentioning
confidence: 99%